Penerapan Hukum Adat Sasi Laut Dalam Melindungi Kelestarian Sumberdaya Alam Laut Di Desa Waria Kecamatan Aru Utara Timur Kabupaten Kepulauan Aru - Cidra Wati Sorloy; Jenny Kristiana Matuankotta; Novyta Uktelseja (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The application of marine sasi customary law is an effort to increase marine natural resources so that they can develop both biological and vegetable resources that are conserved within a certain period to develop growth and development for satisfactory results.Purposes of the Research: This study aims to know and examine how the regulation of sasi marine customary law in its application to the protection of the preservation of marine natural resources in the Waria Village of North East Aru (Batuly) Kepuluan Aru Regency. Methods of the Research: This writing was carried out with the type of empirical juridical research, namely research conducted to obtain data through observation, interviews, documentation, library studies.Results of the Research: The results of the study show that national regulations have not been able to anticipate technological developments and the development of legal needs in the context of managing and utilizing the potential of marine natural resources. The application of the customary law of the sea sasi plays an important role as an effort to protect and preserve marine natural resources.